INCREASING FITNESS WITH ACUPUNCTURE AND HERBS - Imandiri, Ario; Pratama, Diarista Salfa; Rahman, Abdul (Journal of Vocational Health Studies, 2020)
Background: Fitness is the state of the body does not experience significant fatigue after doing routine activities. While in Traditional Chinese Medicine (TCM), fitness is defined as the good circulation of Qi-energy and Xue-blood that can cause the function of the organs of Zhang Fu to run well. Physical predisposition is influenced by various factors and assessed in various ways, one of which is by measuring VO2 max calculated by doing cooper test that is running for 12 minutes on the track 400 meters. A person's VO2 max level indicates the level of physical fitness. Based on the examination that has been done, the patient is exposed to excessive heat pathogens in the Stomach, there are humid pathogens in the body, and Qi and Xue are not sufficient. Purpose: To find out the effect of acupuncture therapy and herbal administration in complementary traditional medicine on improving fitness. Method: To improve fitness is done acupuncture therapy and herbal therapy. Acupuncture therapy is performed at the Zusanli point (ST 36) and Sanyinjiao point (SP 6). Herbal therapy given during treatment is infusion of leaves Gotu Kola (Centella asiatica (L). Urb) and Liquorice (Glycyrrhiza glabra L.). To improve fitness, acupuncture therapy was performed 12 times in 4 stages of therapy. For herbal therapy infusa leaves Gotu Kola fresh as much as 2.5 grams and 2 grams of Liquorice, taken daily 3 times a day. Results: Acupuncture and herbal therapy that has been done for 26 days showed good results. This is evidenced by the results of copper test VO2 max increased 44.3% and no more complaints felt by patient. Conclusion: Acupuncture therapy at the point of Zusanli (ST36), Sanyinjiao (SP6) accompanied by gotu kola herbs (Centella asiatica (L.) Urb) and liquorice (Glycyrrhiza glabra L.) can improve fitness.